2014
DOI: 10.1186/1471-2253-14-96
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different flow patterns and end-inspiratory pause on oxygenation and ventilation in newborn piglets: an experimental study

Abstract: BackgroundHistorically, the elective ventilatory flow pattern for neonates has been decelerating flow (DF). Decelerating flow waveform has been suggested to improve gas exchange in the neonate when compared with square flow (SF) waveform by improving the ventilation perfusion. However, the superiority of DF compared with SF has not yet been demonstrated during ventilation in small infants. The aim of this study was to compare SF vs. DF, with or without end-inspiratory pause (EIP), in terms of oxygenation and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Minimum positive end-expiratory pressure (PEEP) was standardized at 5 cm H 2 O unless the patient had severe chronic obstructive pulmonary disease or clinical evidence of auto-PEEP. Ideal PEEP was determined on a standardized PEEP decrement trial as previously described [15]. Isotonic crystalloids were used to treat hypotension in fluid responsive patients; vasoactive agents were used in patients deemed to be euvolemic.…”
Section: Eras Protocol Development and Pathwaymentioning
confidence: 99%
“…Minimum positive end-expiratory pressure (PEEP) was standardized at 5 cm H 2 O unless the patient had severe chronic obstructive pulmonary disease or clinical evidence of auto-PEEP. Ideal PEEP was determined on a standardized PEEP decrement trial as previously described [15]. Isotonic crystalloids were used to treat hypotension in fluid responsive patients; vasoactive agents were used in patients deemed to be euvolemic.…”
Section: Eras Protocol Development and Pathwaymentioning
confidence: 99%
“…Roth et al [25] reported that decelerating inspiratory flow had no beneficial effects on pulmonary gas exchange when compared with the square inspiratory flow while an increase in mean airway pressure in pressure-controlled ventilation may raise the potential risk of VILI. Some other experimental studies [26,27] showed that there are no differences between square or decelerating flow waveform in oxygenation. Antonaglia et al mathematical model [28] showed that both ventilatory modes provided similar gas distribution, but in square flow, peak pressures were higher in the sicker compartment respect to decelerating flow.…”
Section: Introductionmentioning
confidence: 94%
“…Roth et al [25] reported that decelerating inspiratory flow had no beneficial effects on pulmonary gas exchange when compared with the square inspiratory flow while an increase in mean airway pressure in pressure-controlled ventilation may raise the potential risk of VILI. Some other experimental studies [26,27] showed that there are no differences between square or decelerating flow waveform in oxygenation. Antonaglia et al mathematical model [28] showed that both ventilatory modes provided similar gas distribution, but in square flow, peak pressures were higher in the sicker compartment with respect to decelerating flow.…”
Section: Introductionmentioning
confidence: 94%